EFFECT OF WATER RESTRICTION ON BODY WEIGHT, FEED INTAKE AND PHYSIOLOGICAL RESPONSES IN BARBARI GOATS1 - MAURYA, C. M.; LAKHANI, G. P.; GHOSH, S.; ROY, B.; JAIN, A. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTTotal of 18 Adult female Barbari goats of identical body weight and size were selectedto study the effect of water restriction on body weight, feed intake and physiologicalresponses. The goats were distributed randomly in three different groups of 6 in each andassigned three different treatments: control (T1), 15 % water restriction (T2) and 30 % waterrestriction (T3). All the goats were stall fed on concentrate and gram straw. Study wasconducted in two phases, 30 days in each phase (January and April) for total 60 days. Thebody weight reduced by 3.89% when goats are kept in 15% water restriction (T2) and 9.28%when goats kept on 30% water restriction (T3) compared to control group (T1). The dry matterintake was reduced by 8.01% when goats are kept in 15% water restriction (T2) and 19.06%when goats kept on 30% water restriction (T3) compared to control group (T1). There wassignificant effect of water restriction both at 15% and 30% levels on pulse rate and at 30%level on rectal temperature. But, water restriction had no significant effect on respiration rate.Therefore, 15% water restriction is possible in goat without much affecting its performance.Keywords: Barbari goats, water restriction, dry matter, bodyweight, pulse rate, respirationrate, and rectal temperature.